Application of the IMTA (Integrated Multi-Trophic Aquaculture) System in Freshwater, Brackish and Marine Aquaculture - Muhammad Hanif Azhar; Devrim Memiş (Aquatic Sciences and Engineering)
Aquaculture activities that have been carried out intensively for several decades have made this sector grow rapidly compared to other food sectors. However, intensive activities have negative impacts, one of which is on the environment. To respond to these problems, aquaculture activities have now focused on environmentally friendly aquaculture by implementing various ecosystem-based cultivation systems and improving aquaculture management based on the principle of sustainable aquaculture. The IMTA (Integrated Multi-trophic Aquaculture) system is a cultivation system that uses species with different trophic levels to reuse wasted nutrients to be used as biomass. Currently, the IMTA system has begun to be developed in various countries in fresh, brackish, and marine water cultivation with multiple approaches according to environmental, social, and economic conditions. This review study discusses different IMTA systems and their applications.